Bilateral sequential lung transplantation for end stage septic lung disease. Issue 5 (May 1995) - Hasan, A; Corris, P A; Healy, M; Wrightson, N; Gascoigne, A D; Waller, D A; Wilson, I; Hilton, C J; Gould, F K; Forty, J
Abstract : BACKGROUND– Bilateral sequential lung transplantation (BSLT) has been widely adopted as an alternative to combined heart and lung transplantation for the management of end stage septic lung disease in many transplant centres. METHODS– A retrospective review was undertaken of the first 32 consecutive patients with septic lung disease to undergo BSLT at the Freeman Hospital. RESULTS– Between April 1988 and October 1994 32 patients underwent BSLT. Survival at 30 days was 85% and actuarial survival at one year was 70%. Improved pulmonary function was seen in all surviving patients. CONCLUSION– BSLT for septic lung disease offers comparable survival to heart-lung transplantation, with excellent functional results. Long term results may be superior because the disadvantages of transplanting the heart are avoided.